An integrated decision driven design framework to support the ecological restoration of rivers. Issue 8 (3rd July 2022) - King, Myron; van Zyll de Jong, Michael; Piercey, Doug; Nunn, Andy D.; Cowx, Ian G.
Abstract : A structured and collaborative approach to design and decision‐making in the context of ecological restoration of rivers is developed and illustrated using a case study involving the mitigation of physical barriers to fish migration on the River Trent in the UK. The integrated design and decision-making framework provide a practical workflow model for structuring multi‐attribute decisions, engaging stakeholders, and assembling a design team needed to successfully plan environmental interventions. In our implementation team, members included ecologists, fisheries biologists, government scientists, and representatives of key stakeholder groups. The case study demonstrated a values‐based approach to implementing an ecological restoration plan that addresses some of the long‐standing barrier removal goals associated with the reintroduction of Atlantic salmon and European Union (EU) Habitats Directive listed species European lamprey and River eel. The integrated decision-driven, design framework approach is highlighted by trans-disciplinarily and social learning.